Health education about lifestyle-related risk factors in gynecological and obstetric care: a qualitative study of healthcare providers’ views in Germany - Bombana, Manuela; Wensing, Michel; Wittenborn, Lisa; Ullrich, Charlotte (International journal of environmental research and public health, 2022)
Lifestyle-related risk factors (LRRFs) during pregnancy and lactation are associated with a range of health problems. However, previous studies have shown a large knowledge gap among pregnant women regarding the effects of LRRFs. This study aimed to investigate the role of health education about LRRFs during pregnancy and lactation in gynecological and obstetric care from healthcare providers’ (HCPs) point of view.
Gesehen am 08.11.2022